A comparative study of the general secondary curriculum of public schools in the Philippines and in Thailand - Sisthiwong, Yuwadee 1943- ([Quezon City s.n.], 1968)
The extent of the similarities and differences that exist between the 2-2 plan of the general secondary curriculum of public schools in the Philippines and the Thai academic secondary school curriculum is determined by normative survey through content analysis. Comparisons are made in terms of the secondary education's objectives, structure, students, curricular offerings, school time requirements in each subject, practice of curriculum construction, curriculum improvement and curriculum evaluation.
Thesis (M.Ed.)--University of the Philippines
Keywords: Education, Secondary -- Curricula. -- Philippines; Education, Secondary -- Curricula. -- Thailand